Vocabulary Teaching by Words Association - Tryana Tryana; Lida Holida Mahmud (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Vocabulary Teaching by Words Association The research attempts to assist pupils in enhancing their English vocabulary. The study highlighted an approach for teaching vocabulary by boosting Words Association. It emphasized the importance of memorizing in enhancing pupils' English Vocabulary proficiency. In addition, the study examined the attitudes and behaviors of students towards the use of Words Association in vocabulary instruction. Since the goal of this study is to determine if Words Association is beneficial for Vocabulary Teaching, the study investigated the extent to which Words Association motivates students to participate in their vocabulary recall. The study also studied the impact of Words Association on students' performance on the Vocabulary mastery through Words Association examination. The literature review was centered on the teaching of vocabulary acquisition in an Indonesian context, which was then tied to the memorizing of words through word association. In addition, a qualitative approach was employed through class research. In addition, 32 students from the university's Vocabulary class were selected for the investigation. In addition, the study included a pre- and post-Vocabulary evaluation with the purpose of enhancing students' vocabulary abilities, which were then linked to their perceptions and emotions. This study revealed that Words Association is an effective approach for enhancing vocabulary. However, it firstly come to strengthening student’s memorization through comprehending in context then giving positive result to students’ vocabulary achievement.